An Analysis of Error Pronounciation in Arabic Vocabulary by Blind Students/تحليل الأخطاء في نطق المفردات العربية للتلاميذ المكفوفين - Erawati, Erawati (UIN Raden Mas Said Surakarta, 2020)
This study aims to describe the pronunciation errors of vocabulary and the factors causing the pronunciation errors of vocabulary that are read by blind students at MAN 2 Klaten. The method used for this research is descriptive qualitative research. The data collection methods used by researchers to access the data required in the writing of this study are the observation method, the interview method, and the documentation method. From this research, it is known that some of the mistakes made by students include errors in ibdal, hadzf, and idhafah. The factors causing the mispronunciation of vocabulary that are read by blind students are 1) The difference between the two languages in the al-letter makhariju; 2) Students cannot see the teacher who gives examples of vocabulary pronunciation; 3) A hearing mechanism that differentiates sound pronunciation; 4) Blind students do not know the meaning of vocabulary.